Analysis Of Work Motivation, Work Environment And Work Discipline On The Performance Of PTPN III Bandar Selamat, Asahan District, Security Section - Abdi Setiawan; Teguh Wahyono; Afifah Rizky Naibaho (International Journal of Management, Economic and Accounting, 2023)
This study investigates the impact of performance-related factors, namely work motivation, work environment, and work discipline, on the performance of employees in the Security Section of PTPN III Bandar Selamat, Asahan District. Utilizing a quantitative approach and employing multiple linear regression analysis with SPSS program version 20.0, the study involved 46 respondents from the target population. The findings reveal that work motivation significantly influences the performance of PTPN III Bandar Selamat employees in the Asahan District Security Section (tcount=2.600, p=0.013), affirming a positive correlation. Similarly, the work environment demonstrates a significant positive effect on employee performance (tcount=2.069, p=0.045), indicating that a conducive work environment contributes to enhanced performance. On the other hand, work discipline is found to be insignificant in influencing employee performance (tcount=0.550, p=0.585), suggesting that adherence to work discipline does not significantly impact performance. When considering these factors collectively, the study establishes that work motivation, work environment, and work discipline jointly exert a positive and significant influence on employee performance (Fcalculate=28.944, sig. 0.000). This indicates that the combined impact of these factors is more substantial than their individual effects. In summary, the study underscores the importance of fostering work motivation and maintaining a positive work environment to enhance employee performance. While work discipline alone may not significantly impact performance, a comprehensive approach considering all three factors can contribute to a more effective and productive workforce in the Security Section of PTPN III Bandar Selamat, Asahan District.